Open and Distance Learning in French-Speaking Sub-Saharan Africa: A Literature Review - Emmanuel Béché (Athabasca University Press, 2018)
This article is a literature review on open distance learnings (ODL) in Francophone Sub-Saharan Africa (FSSA). The state of research on this question highlights many topics, such as the supporting reasons for the creation of ODL systems and their potentials. Success, difficulties, and issues linked to their implementation also hold a crucial place in this research. Besides, this literature review shows that studies on ODLs in FSSA emphasize the representations, motivations, and identities of students and university managers, including the historical and cooperative aspects of these third-generation learnings. While most of the research in this field are descriptive or exploratory, others are critical. Beyond these results, research must further explore many perspectives, mainly those related to teaching and learning practices, evaluation, social and university transformations, and the hybrid forms of learning.